Isolation and Identification of a Novel Phlebovirus, Hedi Virus, from Sandflies Collected in China - Ziqian Xu; Na Fan; Xin Hou; Jing Wang; Shihong Fu; Jingdong Song; Mang Shi; Guodong Liang (Viruses, 2021)
We report the isolation of a newly recognized phlebovirus, Hedi virus (HEDV), from Phlebotomus chinensis sandflies collected in Shanxi Province, China. The virus’ RNA is comprised of three segments. The greatest amino acid sequence similarity of the three gene segments between this virus and previously recognized phleboviruses is 40.85–63.52%, and the RNA-dependent RNA polymerase (RdRp) amino acid sequence has the greatest similarity (63.52%) to the Rift Valley fever virus (RVFV) ZH-548 strain. Phylogenetic analysis of the amino acid sequence of the virus RdRp indicated that HEDV is close to RVFV and distinct from other phleboviruses, forming its own evolutionary branch. We conclude that it is necessary to increase the monitoring of phleboviruses carried by sandflies in China.